Submeso Motions within the Stable Boundary Layer and Their Relationships to Local Indicators and Synoptic Regime in Moderately Complex Terrain - Hoover, Joshua D.; Stauffer, David R.; Richardson, Scott J.; Mahrt, Larry; Gaudet, Brian J.; Suarez, Astrid (Journal of applied meteorology and climatology, 2015)
To better understand the physical processes of the stable boundary layer and to quantify “submeso motions” in moderately complex terrain, exploratory case-study analyses were performed using observational field data supplemented by gridded North American Regional Reanalysis data and Pennsylvania State University real-time Weather Research and Forecasting Model output. Submeso motions are nominally defined as all motions between the largest turbulent scales and the smallest mesoscales. Seven nighttime cases from August and September of 2011 are chosen from a central Pennsylvania [“Rock Springs” (RS)] network of eight ground-based towers and two sound detection and ranging (sodar) systems. The observation network is located near Tussey Ridge, ~15 km southeast of the Allegheny Mountains. The seven cases are classified by the dominant synoptic-flow direction and proximity to terrain to assess the influence of synoptic conditions on the local submeso and mesogamma motions. It is found that synoptic winds with a large crossing angle over nearby Tussey Ridge can generate mesogamma wave motions and larger-magnitude submeso temperature and wind fluctuations in the RS network than do winds from the direction of the more distant Allegheny Mountains. Cases with synoptic winds that are nearly parallel to the topographic contours or are generally weak exhibit the smallest fluctuations. Changes in the magnitude of near-surface submeso temperature and wind fluctuations in response to local indicator variables are also analyzed. The observed submeso wind and temperature fluctuations are generally larger when the low-level wind speed and thermal stratification, respectively, are greater, but the synoptic flow and its relation to the terrain also play an important role.